Food-For-All Web Application for Donation Management - Yasith Chandula; Akila Kavinda; Thushal Shaminda; Sachintha Gunaratne; D.I. De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
Food is a vital need for all human beings. But in the current society, many people cannot afford or fulfill their daily food requirements. Many people want to help people who are in hunger, but the problem is there isn’t a good and trustworthy platform to get information and connect the donator and the receiver that is available for Sri Lanka. The application's main purpose is to bring together individuals who have excess assets and liabilities and are eager to give back to the community to help those who are in need and willing to accept help and also provides a platform to post about those in need of food and other related things. Another advantage of this system is that it allows organizations to create funds within the system and raise funds for their charitable projects related to food insecurity and improving agriculture. The system always tries to avoid fake and fraudulent donations and requests by asking the approval of the admins. It also helps in improving the reliability and the trustworthiness of the users of the system. For an example organizations need to be verified by the admin to use the system. Also, each fundraiser program created by the registered organization will be reviewed by the admin before publish it in the system.